Choice among Lotteries when Preferences are Stochastic - John K. Dagsvik (Statistics Norway, Research Department, 1998)
This paper discusses the problem of specifying probabilistic models for choices (strategies) with uncertain outcomes. The point of departure is an extension of the axiom system of the von Neumann-Morgenstern Expected utility theory to the case when the preferences are stochastic. This extended axiom system is combined with Luce Choice Axiom; "Independence from Irrelevant Alternatives", and imply a particular choice model that contains the Luce model as a special case. An additional invariance assumption is subsequently proposed that yields a complete characterization of the mathematical structure of the model.
Keywords: C25; D11; D81; 330; Random tastes; choice among lotteries; random utility models; bounded rationality; probabilistic choice models; independence from irrelevant alternatives.